Cancer pain: neurosurgical strategies - Meglio, Mario; Cioni, Beatrice; Morales, Andreas; Visocchi, Massimiliano (Medicina e Morale, 1989)
In common understanding, the term "pain" can take on different meanings: that of a specific sensation as a result of bodily evil, that of a feeling or state of deep unhappiness due to dissatisfaction of individual needs, aspirations or tendencies, that of an event or thing that produces pain, torment. Each of us uses this word to express different feelings, emotions or states of mind, making the problem of defining pain not easy to solve.